THE STRATEGIC DIMENSION OF THE ERISTIC DIALECTIC IN THE CONTEXT OF THE GENERAL THEORY OF CONFRONTATIONAL ACTS AND SITUATIONS - HORDECKI, Bartosz (Przegląd Strategiczny, 2018)
This paper attempts to describe the strategic dimension of the eristic dialectic, which is frequently defined as the art of the dispute. This goal is embedded in reflections on the general theory of confrontational acts and situations. The text stresses the fact that strategic thinking about the art of discussion is not given sufficiently deep consideration. Another observation pertains to the fact that the essence of the strategic design of discussions lies in the analysis of long-term results, which can be attained in the course of the exchange of arguments. At the same time, this analysis must not be limited exclusively to identifying the objectives of the discussion or the means of attaining them. Argumentative strategy also includes reflection on the side effects, both positive and negative, which may be the product of a specific communication practice.